At the Heart of the Pregnancy: What Prenatal and Cardiovascular Genetic Counselors Need to Know about Maternal Heart Disease. Issue 4 (10th March 2017) - Morales, Ana; Allain, Dawn C.; Arscott, Patricia; James, Emily; MacCarrick, Gretchen; Murray, Brittney; Tichnell, Crystal; Shikany, Amy R.; Spencer, Sara; Fitzgerald‐Butt, Sara M.; Kushner, Jessica D.; Munn, Christi; et al.
Abstract: In the last decade, an increasing number of cardiac conditions have been shown to have a genetic basis. Cardiovascular genetic counseling has emerged as a subspecialty aiming to identify unaffected at‐risk individuals. An important sector of this at‐risk population also includes expectant mothers, in whom unique clinical challenges may arise. Genetic counselors, especially those in cardiovascular and prenatal settings, have an opportunity to identify and assist women who may benefit from cardiovascular care during pregnancy. This paper provides basic management and genetic evaluation principles for affected women, as well as guidance on identifying those who are at risk. We provide considerations for cardiac surveillance in pregnancy and the post‐partum period. Finally, key psychosocial issues that appraise how to best provide support to at risk women as they make informed decisions are discussed. We propose that a team approach including cardiology, maternal fetal medicine, and genetic counseling best serves this patient population. Ongoing questions addressing an evidence based approach to cardiovascular genetic conditions in pregnancy still remain. Thus, well‐designed research protocols are essential to mark progress in this area.